Socialization of Corruption Criminal Prevention with the Tulungagung State Ago - Sofyan Wimbo Agung Pradnyawan; Sulistya Eviningrum; Dimas Pramodya Dwipayana; Agung Tri Raditya (Jurnal Pengabdian Masyarakat Bestari, 2022)
That this research aims to find out to what extent the community and stakeholders play a role in eradicating corrupt behavior in order to prevent criminal acts of corruption through non-penal measures. Development as a planned effort for the people's welfare, it has been endeavored as efficiently and as possible as effectively as possible with funds and limited capabilities. However, is in active development held, news emerged about rampant corruption cases, which done with the modus operandi increasingly sophisticated, Corruption and abuse of office is an administrative disease can be eradicated as long as we have strong commitment to handle it.The research method in this case uses the empirical research method by displaying supporting primary and secondary data. The results of the research arecorruption, constitutes abuse and misappropriation, which is committed by state administrators of money or state facilities, this is where the role of the prosecutor can be optimized to carry out administrative action, in the form of prevention that can be optimized to eradicate corruption which is expected to produce more tangible results.